Assessment of the significance of factors associated with the development of long-term adverse cardiovascular events in type 2 diabetes mellitus - D. V. Grazhdankina; I. A. Bondar; A. A. Demin (Лечащий Врач, 2022)
To study the factors associated with the development of long-term major adverse cardiovascular events (MACE), 94 patients with type 2 diabetes mellitus (T2D) aged 40-65 years (65% of women) with eGFR > 60 ml/min/1,73 m2 and without manifestations of moderate or severe chronic heart failure (CHF) were examined. In patients with T2D clinical and laboratory data were evaluated. A 6-minute walk test (6MWT) and echocardiography were performed. Concentration of N-terminal pro-brain natriuretic peptide (NTproBNP) was determined on an Immulait 2000 Siemens analyzer by immunochemiluminescence assay. Glycemic variability was assessed by calculating the standard deviation (SD) and coefficient of variation (CV) of glycemia during the day according to laboratory measurements of glucose levels at least 3 times a day for at least 3 days. The initial manifestations of CHF according to the clinical examination were detected in 40 out of 94 patients with T2D. According to the discriminant analysis results, they were interconnected with the presence and duration of stable coronary heart disease, an increase in the left ventricle posterior wall thickness and the left atrial (LA) size, an increase in triglyceride level, an increase in duration of diabetes, and a lower estimated glomerular filtration rate. A relationship was found between the initial manifestations of CHF and an increase in CV glycemia during the day and the presence of episodes of hypoglycemia in history. After 8.8 ± 0.72 years MACE were found in 38.6% of patients with T2D (n = 88). There were 12 deaths (10 of them from cardiovascular diseases), 5 cases of myocardial infarction, 9 cases of emergency myocardial revascularization, 4 cases of stroke, 4 cases of hospitalization due to decompensation of CHF. The relationship between MACE and the initial increase in the level of NT-proBNP, an increase in the LA size, and a decrease in 6MWT values was determined according to logistic regression analysis with a percentage of correct prediction of 81.9%. The development of long-term MACE in T2D patients was also influenced by the presence of episodes of hypoglycemia in history and increased glycemic variability. This was confirmed by the logistic regression analysis, which showed the relationship between the development of new cardiovascular complications and death with an initial increase in intraday glycemic CV, an increase in the LA size, and the presence of initial manifestations of CHF with a percentage of correct prediction of 87.8%. After 8.8 ± 0.72 years, 41 patients with type 2 diabetes underwent a repeated clinical and laboratory study and echocardiography with an assessment of left ventricular diastolic function (LV DD) according to the criteria of the RSC for CHF 2020. LV DD was detected in 51,2% of T2DM patients and was correlated with the initial increase in the level of NT-proBNP, especially in combination with the initial increase in the left ventricular myocardial mass index and body mass index according to the results of logistic regression analysis. The level of NT-proBNP more than 31.2 pg/ml can be considered as a prognostic marker of LV DD in T2D patients after 8.8 ± 0.72 years of followup with a sensitivity of 66.7% and a specificity of 100%.